2015
DOI: 10.2337/db15-0770
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA-29 Family Dictates the Balance Between Homeostatic and Pathological Glucose Handling in Diabetes and Obesity

Abstract: The microRNA-29 (miR-29) family is among the most abundantly expressed microRNA in the pancreas and liver. Here, we investigated the function of miR-29 in glucose regulation using miR-29a/b-1 (miR-29a)-deficient mice and newly generated miR-29b-2/c (miR-29c)-deficient mice. We observed multiple independent functions of the miR-29 family, which can be segregated into a hierarchical physiologic regulation of glucose handling. miR-29a, and not miR-29c, was observed to be a positive regulator of insulin secretion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
127
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(149 citation statements)
references
References 26 publications
13
127
0
1
Order By: Relevance
“…miR-29a-3p-deficient mice have dysregulated exocytosis, promoting diabetes after unfolded protein stress [41]. Increased glucose levels upregulated miR-29a-3p in rat and human islets, while miR-29a-3p inhibited glucose-stimulated insulin secretion and increased proliferation of INS-1E beta cells [42].…”
Section: Discussionmentioning
confidence: 99%
“…miR-29a-3p-deficient mice have dysregulated exocytosis, promoting diabetes after unfolded protein stress [41]. Increased glucose levels upregulated miR-29a-3p in rat and human islets, while miR-29a-3p inhibited glucose-stimulated insulin secretion and increased proliferation of INS-1E beta cells [42].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, both miR-29a and miR-29c serve as negative regulators of insulin signaling via phosphatidylinositol 3-kinase (PI-3K) regulation. Global or hepatic insufficiency of miR-29 retards obesity and dietinduced insulin resistance (Dooley et al, 2016). Moreover, miRNAs are directly linked to inflammation and adiposity.…”
Section: Noncoding Rnamentioning
confidence: 99%
“…Our study was aimed to link miRNA regulation with lipid overload and the immunoinflammatory mechanism of AS. Many recent studies have found that miR-29a was involved in numerous biological processes, including AS (Liu et al, 2017), hepatocellular carcinoma (Parpart et al, 2014), myocardial fibrosis (Dai et al, 2014), glucose handling (Dooley et al, 2016), and so on. Nowadays, researchers have found that plasma miR-29a was a new biomarker that could play a role in the pathophysiology of AS (Hulsmans and Holvoet, 2013;Huang et al, 2016;Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%